Foliar application of chitosan on growth and yield attributes of mungbean (Vigna radiata (L.) Wilczek) - Mondal, MMA; Malek, MA; Puteh, AB; Ismail, MR (Bangladesh Journal of Botany, 2013)
Plant parameters such as plant height, branch and leaf number/plant, leaf area/plant, total dry mass/plant, photosynthesis, harvest index, chlorophyll, nitrate reductase and number of pods/plant increased significantly with the increasing concentration of chitosan up to 50 ppm. It resulted the highest seed yield in mungbean. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15910 Bangladesh J. Bot. 42(1): 179-183, 2013 (June)